2018
DOI: 10.1111/wej.12359
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of coagulation‐ultrafiltration performance for the treatment of primary wastewater using alum sludge

Abstract: The main purpose of this research was to develop an effective and inexpensive pretreatment for ultrafiltration (UF) membrane process in order to treat a primary effluent for its reuse in several applications by avoiding biological treatment. For that the impacts of reuse alum sludge liquid recovered by the drinking water treatment plant of Boudouaou (Algiers area) has been examined on the water quality in coagulation–sedimentation processes. The tests were carried out on a primary effluent of wastewater treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The sludge has also been used as a coagulant in wastewater treatment plants (WWTPs) [88][89][90]. WTS applied in the post-treatment of upflow anaerobic sludge blanket (UASB) reactor effluents provided high removal efficiencies in terms of biochemical oxygen demand (BOD) (78%), chemical oxygen demand (COD) (74%) and suspended solids (SS) (84%), suggesting that this application is a promising option [91].…”
Section: Water Treatmentmentioning
confidence: 99%
“…The sludge has also been used as a coagulant in wastewater treatment plants (WWTPs) [88][89][90]. WTS applied in the post-treatment of upflow anaerobic sludge blanket (UASB) reactor effluents provided high removal efficiencies in terms of biochemical oxygen demand (BOD) (78%), chemical oxygen demand (COD) (74%) and suspended solids (SS) (84%), suggesting that this application is a promising option [91].…”
Section: Water Treatmentmentioning
confidence: 99%
“…It has also been used as a special coagulating and flocculating agent for industrial effluent purification [32]. Hu et al [33] used liquid AlS as a coagulant for pesticide immobilization in wastewater, while Mazari et al [34] introduced liquid AlS into the pre-treatment process as the primary coagulant for the ultrafiltration (UF) membrane process of municipal wastewater treatment. Shrestha et al [35] also used waterworks AlS in pilot sewers for the first time to replace chemical coagulants.…”
Section: As Coagulant For Wastewater Treatmentmentioning
confidence: 99%
“…Hu et al [55] used liquid AlS as coagulant for pesticide immobilization in wastewater and found that the liquid AlS adsorbed P more rapidly than dewatered AlS cakes as well as having higher performance in comparison with other adsorbents. Mazari et al [56] introduced liquid AlS into the pre-treatment process as the primary coagulant for the ultrafiltration (UF) membrane process of municipal wastewater treatment. Shrestha et al [57] also used waterworks AlS in pilot sewers for the first time to replace the chemical coagulants.…”
Section: Wts Used As Substrate In Developing Constructed Wetland Treamentioning
confidence: 99%